FILOSOFI KEKUASAN DAN POLITIK DALAM ORGANISASI - Abdul Wahid Mahsuni; Wardani, Navilah Laila; Moch Ardiansyah Pramudya; Maharani Ulya Fadhilah; Ahmad Fajar Irianto (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Power is used as the basis of politics, where individuals or groups try to use it to achieve personal or group goals. The purpose of this study is to investigate the role of power and politics in an organizational context, as well as to understand how the distribution of power, the use of politics, and the dynamics of power and politics can affect organizational performance. The research method in this article uses library research, which is a study that studies various reference books as well as the results of previous similar research that is useful for obtaining a theoretical basis for the problem to be studied. power and politics play an important role in organizations. Power can appear in various forms, such as formal power related to hierarchical positions and informal power related to interpersonal influence. Organizational politics involves the efforts of individuals or groups to utilize their power to achieve personal or group goals. Keyword : Power, Politics, Organization